Healthcare design assessment using semi-automated approaches for code checking - Soliman-Junior, Joao; Tzortzopoulos, Patricia; Kagioglou, Mike (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
This paper reports initial research findings exploring the assessment of regulatory requirements in the healthcare design process, using different levels of automation – code checking. The methodological approach is Design Science Research, with an empirical study undertaken in close collaboration with an institution responsible for Primary Healthcare buildings in the UK. The main findings include understanding that the design of healthcare projects is intrinsically subjective, which is also reflected by the way regulations for healthcare buildings are developed. Thus, automated approaches for design assessment will only be suitable for the healthcare context if such approaches enable the consideration of requirements subjectivity. In fact, this consists of a change in the way subjectivity is considered in code checking research, which has traditionally been seen as problematic for the design assessment process, due to individual biases and potential misunderstandings. This research proposes that subjectivity in design assessment should be understood in terms of how its negative effects could be alleviated, but at the same time understanding it supports creativity and the uniqueness of human reasoning during the healthcare design process.